La nozione di filosofia prima in Husserl e nella tradizione filosofica - Costa, Vincenzo (Bollettino Filosofico, 2024)
In the transition from descriptive phenomenology to transcendental phenomenology, the Husserlian notion of philosophy takes on the aspect of a first philosophy. It indicates a field of “preliminary” research, which comes first, since it must clarify the concepts that all sciences use, as well as the relations that the various regional ontologies entertain. This outlines the Husserlian notion of first philosophy. In the last part of the paper, we try to highlight the structural differences that separate it from the notion of first philosophy in Aristotle, Descartes and Hume. Keywords: First Philosophy, Insight, Metaphysics, Phenomenology, Subjectivity